1979
DOI: 10.1002/cpt1979256783
|View full text |Cite
|
Sign up to set email alerts
|

Indoramin and prazosin as adjuncts to beta adrenoceptor blockade in hypertension

Abstract: Two trials were conducted on the effects of adding alpha-adrenoreceptor blockers to the therapy of hypertensive patients already receiving a beta-adrenoreceptor blocking drug with or without a diuretic. The first trial was a single-blind study in which 6 patients receiving long-term combination therapy were crossed from prazosin, 6 to 15 mg/day, to a dose of indo ram in 10 times as large. There was significant bradycardia but little change in blood pressure. The second trial was a double-blind randomized cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…In vitro studies by previous in vestigators [Schoetensack et al, 1977b] showed that urapidil is a competitive his tamine Hpantagonist sharing this prop erty with other substituted piperazines like cyclizine, chlorcyclizine and mecli zine as prototypes of this class of H|-blockers. A similar action has been found for drugs possessing the chemically related piperidyl group like the ai-adrenoceptor antagonist indoramin which has been shown to exhibit bronchodilating ac tivity in vitro and in vivo [Alps et al, 1972;Bianco et al, 1974;Stokes et al, 1979). This effect is only partly explained by its a-adrenoceptor antagonism but also by prevention of the bronchoconstrictor re sponse to endogenous histamine and se rotonin [Black et al, 1978).…”
Section: Introductionmentioning
confidence: 77%
“…In vitro studies by previous in vestigators [Schoetensack et al, 1977b] showed that urapidil is a competitive his tamine Hpantagonist sharing this prop erty with other substituted piperazines like cyclizine, chlorcyclizine and mecli zine as prototypes of this class of H|-blockers. A similar action has been found for drugs possessing the chemically related piperidyl group like the ai-adrenoceptor antagonist indoramin which has been shown to exhibit bronchodilating ac tivity in vitro and in vivo [Alps et al, 1972;Bianco et al, 1974;Stokes et al, 1979). This effect is only partly explained by its a-adrenoceptor antagonism but also by prevention of the bronchoconstrictor re sponse to endogenous histamine and se rotonin [Black et al, 1978).…”
Section: Introductionmentioning
confidence: 77%
“…The use of ganglion blockers, adrenergic neurone blockers and centrally acting agents has declined whilst P-adrenoceptor blocking agents have been used widely. It is now recognized that whereas P-blockade reduces blood pressure, a secondary rise in the peripheral resistance may occur (Frohlich et al, 1968) and the use of an a-blocking agent in combination with P-blockade has been advocated (Beilin & Juel-Jensen, 1972;Stokes et al, 1979). Indoramin is a post-synaptic a-receptor blocking agent which has been shown to possess modest hypotensive activity (Coltart, Meldrum & Royds, 1971;Royds, Coltart & Lockhart,1972;Lewis, George & Dollery, 1973), when assessed by the indirect method of blood pressure recording.…”
Section: Discussionmentioning
confidence: 99%
“…It was surprising finding that the plasma renin activity became slightly elevated. Previous workers [12,13] did not observe this change in essential hypertensives. The results suggest that indoramin caused afferent arteriolar vasodilation and thereby altered the local renal autoregulatory re sponse so that renin in the juxtamedullary apparatus tended to be discharged into the peripheral circulation [32].…”
Section: Discussionmentioning
confidence: 86%
“…It acts as a competitive adrenoreceptor blocker on the alpha-1 postsynaptic receptors [9], It lowers blood pressure by causing peripheral vasodilation but without a fall of cardiac out put [10], reflex tachycardia [11] or a rise in plasma renin activity [12,13], In trials performed to date there have been no findings that were suggestive of any adverse renal effects and as a vasodilator it should improve renal blood flow, although a previous study using a smaller intravenous injection of indoramin has showed no effect on effective renal plasma flow [14],…”
Section: Introductionmentioning
confidence: 99%